Urgensi Percepatan Pengesahan Rancangan Undang-Undang Penghapusan Kekerasan Seksual - Hardianti, Firda Yanis; Efendi, Reno; Lestari, Putri Diah; Puspoayu, Elisabeth Septin (Jurnal Suara Hukum, 2021)
According to the Annual Report of the National Commission on Anti-Violence Against Women, cases of sexual violence continue to increase each year. The data shows that Indonesia needs regulations that protect victims of sexual violence. So far there has been no legislation that accommodates the whole of crimes and sexual violence resulting in a vacancy and uncertainness of the law. Indonesia needs laws that can complement its special nature governing and carrying out all forms of sexual violence (lex specialis propensionem sexualem identitatemque). So the existence of laws specifically governing sexual violence is critical to providing guaranteed protection and legal certainty for victims of sexual violence in a more perfect range. The withdrawal of the MCC Bill from Prolegnas is clearly not the answer to the growing problem of sexual violence. So by conducting this research will be a clue to the urgency of the Sexual Violence Elimination Bill which encourages the certainty of legalization. This research conducted by library review method which will produce a research analysis of the impact that will occur due to the delay in the ratification of the MCC Bill with the enactment of the Criminal Law Bill (RKUHP) as it is currently.